Trend Kunjungan Wisatawan Mancanegara di Kawasan Konservasi Taman Nasional Teluk Cenderawasih dengan Wisata Minat Khusus Hiu Paus (Rhincodon typus) - Boby Yehezkiel; Ben G. Saroi; Maria Maria; Ricardo F. Tapilatu (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Tourist areas have a significant role in several aspects including economic, social and environmental. The national park has a considerable potential in the aspect of tourism. In addition to having mega biodiversity, the Cenderawasih Bay National Park (TNTC) also has a strong special attraction in term of whale shark, available year-round. Therefore, foreign tourism potential at TNTC is very high and much in demand by both local and foreign tourists. By processing visitation data, we were able to obtain trend and potentials in supporting the carrying capacity of whale shark tourism areas. Through these data, the estimated number of visitors in 2020 at TNTC was also obtained. Data were performed by country grouping and quantified the number of tourists visiting TNTC. By determining the number of foreign visitors, it was found out the intensity of the visit of each country and also countries which are targeted for TNTC’s future promotions. Countries with high intensity visit are suitable for future promotion targets including Australia, USA, UK, Germany and Switzerland.